The Impact of the Breakdown of the Sidoarjo Mud Dam on the Northeast Side Using the HEC-RAS Program - Abdurahman Hafizudin; Budijanto Widjaja (International Journal of Engineering Continuity, 2026)
The eruption of the Sidoarjo mud, commonly known as the Lapindo mudflow, has continuously dumped slurry since 2006, necessitating the construction of an emergency containment embankment with limited engineering control and a high risk of structural failure. One of the critical locations is the northeast embankment segment (P.75), which is located near the residential zone of South Kalitengah, Gempolsari Village. This study aims to predict the flow direction and the level of impact of mud inundation if there is a breakdown of the embankment. Five dam breakdown simulation scenarios were performed using HEC-RAS by varying the Liquid Limit Index (LI), with the material behavior modeled as a non-Newton Bingham flow characterized by viscosity and yield stress parameters, supported by DEM based topography, Manning coefficients derived from land cover, and inflow hydrographs. The results showed that higher LI values led to slower settling times, longer and wider flow paths, shallower flow depths, and much larger inundation areas, extending to the residential sector. The simulated transport and deposition metrics were aligned with previously documented mudflow events, although the flat local topography led to slower accumulation. This study contributes an empirical LI-based rheological-hydrodynamic relationship to predictive hazard modeling and provides important insights for regional risk mitigation, emergency evacuation planning, and embankment strengthening strategies in mud volcanic disaster zones. In addition, a scenario-based sensitivity and uncertainty analysis was performed to assess the influence of rheological variations, surface roughness, and hydrographic parameters on inundation area and maximum depth, so that the interpretation of the results can be placed in the context of input limitations and numerical assumptions.